Pelatihan Tata Cara Membatik Tema Ekosistem Mangrove bagi Pengelola Wisata Alam Cisiu: Training on Mangrove Ecosystem Theme Batik for Natural Tourism Managers - Fuad, Mochamad Arif Zainul; Harlyan, Ledhyane Ika; Purwanti, Pudji; Hidayati, Nurin; Rahmawati, Andira; Masdian, Nuril Haq Bilqishima; Prasetio, Rachmat Ramadhan; Putra, Valeryan Ramana; Rahmanissa, Aulia Intan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The sustainable management of mangrove ecotourism requires generating additional income for its managers. One potential strategy is batik training using mangrove ecosystem motifs. On September 15, 2024, a batik training session was conducted for tour guides and managers of the Mangrove Cisiu Eco-Education Park, located in Pangkah Kulon Village, Gresik. The event was attended by 10 participants and was part of the Community Partnership Program (PKM) titled "Empowering Mangrove Managers through Eco-tourism Package Programs as Income Generating for the Sustainability of Mangrove Edupark Management on Cisiu Island", funded by DRTPM Kemendikbudristek. The training was led by Ms. Maria Cecilia, owner of Sanggar Lembayung Batik, who has extensive experience in teaching batik to various communities. Participants learned the basic techniques of batik-making, featuring motifs inspired by the mangrove ecosystem, such as Glodong fish, crabs, and mangrove trees. The training included canting techniques, wax application, and dyeing with synthetic batik dyes. In addition to technical skills, participants gained insight into the potential of batik as a creative economic product that can serve as an additional income source for ecotourism managers. This training aims to support the economic sustainability of the Mangrove Edupark Cisiu by developing high-value batik products, thus contributing to the preservation of the mangrove ecosystem through enhanced livelihoods for the local community.